Rosa Luxemburg : Periphery and Perception - Jacob, Frank 1984- HerausgeberIn (Büchner-Verlag, 2024)
Rosa Luxemburg was a critical thinker and author of many political and social reflections which to readers of today seem quite up to date. Particularly in the Global South, there seems to exist a stronger interest in Luxemburg’s work today, which is not surprising at all, considering that many problems she thought about are still existent – especially there. The participants of the International Rosa Luxemburg Conference in Bodø, Norway, in March 2023, discussed her role in the 21st century in quite some detail. The present anthology contains the conference’s extended proceedings and particularly focuses on two important elements in regard to Luxemburg: Her role for and within the global ›periphery‹ and her ›perception‹ in relation to other intellectuals, social democracy or the political left in a broader sense of the spectrum